Social Comparison on Multiple Tasks: Sacrificing Overall Performance for Local Excellence? - Maximilian Kohler; Matthias D. Mahlendorf; Mischa Seiter; Timo Vogelsang (Journal of Accounting Research, 2024)
This field experiment investigates how different levels of aggregation in relative performance information (RPI) impact employee performance in environments with multiple tasks. We randomly assign store employees of a retail chain to three groups: RPI on overall performance (control group), RPI on separate tasks, and RPI on both overall performance and separate tasks. We do not find evidence that providing separate task RPI instead of overall RPI affects performance or effort allocation. However, providing RPI on both overall performance and separate tasks seems to reduce performance, especially in the low-return task. This suggests that detailed RPI directs employees' attention to the smaller benefits of low-return tasks. We further find that only 30.5% of the employees accessed their performance reports, highlighting a distinction between providing RPI in the field and the laboratory. This study is based on a registered report accepted by the Journal of Accounting Research .
Keywords: 650; relative performance information; multiple tasks; social comparison; field experiment